2004
DOI: 10.1007/s11908-004-0009-2
|View full text |Cite
|
Sign up to set email alerts
|

Virologic diagnosis, viral monitoring, and treatment of epstein-barr virus infectious mononucleosis

Abstract: Epstein-Barr virus (EBV) is the cause of infectious mononucleosis and is associated with severe infections in immunocompromised patients. EBV is also causally linked with several human malignancies. The heterophile antibody test and EBV-specific antibody tests remain the principal means of diagnosis of initial infection in otherwise healthy patients. Enzyme-linked immunosorbent assays have replaced the traditional immunofluorescence assays for EBV-specific antibodies. Several newer molecular diagnostic tests h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 45 publications
0
15
0
3
Order By: Relevance
“…Dot blotting, Southern blotting, PCR and in situ hybridization have all been applied to various materials, but their differences in sensitivity and specificity have led to the results that need to be considered cautiously [28] as they vary from laboratory to laboratory [73,74] . More recent studies indicate that real-time PCR is particularly sensitive [28] , and very useful for defining infection status, especially in immunocompromised patients [45,75,76] and those at risk of developing EBVrelated disorders [45] . However, there is still no consensus concerning the best material to use, units of measurement, or the quantitative levels requiring intervention or predicting prognosis [16,74,[77][78][79] .…”
Section: Molecular Biologymentioning
confidence: 99%
See 4 more Smart Citations
“…Dot blotting, Southern blotting, PCR and in situ hybridization have all been applied to various materials, but their differences in sensitivity and specificity have led to the results that need to be considered cautiously [28] as they vary from laboratory to laboratory [73,74] . More recent studies indicate that real-time PCR is particularly sensitive [28] , and very useful for defining infection status, especially in immunocompromised patients [45,75,76] and those at risk of developing EBVrelated disorders [45] . However, there is still no consensus concerning the best material to use, units of measurement, or the quantitative levels requiring intervention or predicting prognosis [16,74,[77][78][79] .…”
Section: Molecular Biologymentioning
confidence: 99%
“…However, in immunocompetent patients with acute infection, it is not usually necessary to look for EBV DNA as serology is sufficient except in cases with negative or doubtful serological findings in which there is a strong clinical suspicion of infection [89,97,98] . A search for EBV DNA is particularly important in immunocompromised patients with an incomplete humoral response and patients who have received transfusions or immunoglobulins that confound serological test results [28] . It has been reported that immunocompromised patients have higher baseline viral levels than healthy carriers [99,100] , which decline after treatment.…”
Section: Molecular Biologymentioning
confidence: 99%
See 3 more Smart Citations